The effectiveness of specific health education in providing better quality of life among asthmatic patients at primary care setting in HUSM - Yusof, Yusnita (2006)
The global increase in asthma morbidity requires a closer examination on the aspects of asthma management. The cornerstone of asthma management is achieving adequate symptom control, better quality of life and patient education. The aim of this interventional study was to evaluate the effectiveness of a specific health education programme in the asthmatic patients. Thus, an interventional study was enrolled among asthmatic patients in Klinik Rawatan Keluarga, HUSM from April2004 through end of January, 2005. A hundred and thirty asthmatic patients were recruited, 60 of whom were assigned to the intervention group and another 70 to the control group. The outcomes measured were the quality of life . The Malay version of Asthma Quality of Life (AQLQ) Questionnaire was used to assess the quality of life among the asthmatics. The intervention group attended the programme as scheduled which was conducted individually in the first health education and followed by group counseling of five to tenparticipants each in the second health education. They were carried out in an interactive way. The programme included information about asthma, instruction on the appropriate use of medication and training in the metered dose inhaler (MDI) technique and information about the identification and control of asthma attacks and the recognition of early signs of exacerbation. The control group was submitted to the standard care provided at the clinic, with usual asthmatic advice regarding asthma control. As a result, the intervention group showed significant differences when compared to the control group with respect to the overall quality of life comprising of activity limitations, symptoms, emotional function and environmental stimuli. The global rating of each questionnaire also showed an increase number of those who scored 'better' in the intervention group compared to the control group. However, no significant differences observed in terms of PEFR measurements in the intervention group. It is concluded that the educational programme led to a significant improvement in the quality of life of the asthmatics and the implementation of such programme is possible at the primary care level.